2019
DOI: 10.1371/journal.pone.0218034
|View full text |Cite
|
Sign up to set email alerts
|

Infection free “resisters” among household contacts of adult pulmonary tuberculosis

Abstract: Despite substantial exposure to infectious pulmonary tuberculosis (TB) cases, some household contacts (HHC) never acquire latent TB infection (LTBI). Characterizing these “resisters” can inform who to study immunologically for the development of TB vaccines. We enrolled HHCs of culture-confirmed adult pulmonary TB in India who underwent LTBI testing using tuberculin skin test (TST) and QuantiFERON TB Gold Test-in-tube (QFT-GIT) at baseline and, if negative by both (<5mm TST and <0.35IU/mL QFT-GIT), underwent f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 25 publications
1
35
0
2
Order By: Relevance
“…A hallmark of the natural history of tuberculosis is the diverse outcome of infection. There are three possible outcomes of exposure to an infectious TB case: the infection may be cleared by sterilizing immunity [ 3 ] as evidenced by immunological assays [ 4 ]; development of active TB and development of latent tuberculosis infection (LTBI). Studies have shown that 10% of LTB infected individuals develop active TB and because of the underlying immune deficiency, HIV-infected individuals with LTBI are at 26-fold higher risk for TB reactivation [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A hallmark of the natural history of tuberculosis is the diverse outcome of infection. There are three possible outcomes of exposure to an infectious TB case: the infection may be cleared by sterilizing immunity [ 3 ] as evidenced by immunological assays [ 4 ]; development of active TB and development of latent tuberculosis infection (LTBI). Studies have shown that 10% of LTB infected individuals develop active TB and because of the underlying immune deficiency, HIV-infected individuals with LTBI are at 26-fold higher risk for TB reactivation [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our analyses of HHC at baseline, included additional data that was not available for earlier C-TRIUMPH publications [ 29 , 30 ]. After excluding HHC found to have active TBD at initial screening, baseline characteristics, including characteristics of the TB index patients and households, of the asymptomatic HHC with and without TBD were compared.…”
Section: Methodsmentioning
confidence: 99%
“…This score is composed of a number of questions that provides a good understanding of the extent of exposure (i.e. whether the HHC share the same room or bed as the index case, whether the index case is actively coughing, whether the index case has a smear-positive sputum, whether the index case see the HHC every day) ( 11 , 12 , 15 ). The score can be used in both adult and pediatric populations.…”
Section: Discussionmentioning
confidence: 99%
“…Mave et al. recruited a total of 799 children, adolescents and adults who had been living in the same household of an adult pulmonary TB index case from two different sites in India ( 15 ). Follow-up included three QFT tests and three TSTs (5 TU, PPD, SPAN/Arkray, India) at baseline, at 4 months and at 12 months.…”
Section: Study Designs and Definitionsmentioning
confidence: 99%